Psychological Burden among Caregivers of Children with Autism Spectrum Disorder at Special Schools (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: The alarming increase in the prevalence of autism has cause not only an increase in the number of cases of autism but also increased need for better awareness and understanding of the condition and its management for them who are in direct daily contact with someone with autism. The support for caregivers of autism spectrum disorder children is highly needed to minimize their experienced burden. The objective of this study was to assess the psychological burden among caregivers of children with autism spectrum disorder.MATERIALS AND METHODS: Quantitative non-experimental descriptive research design was adopted for the study. The data was collected from 70 samples with the Modified Zariet Burden Interview Scale. Collection of data was entered into Ms-excel and was analyzed and interpreted using SPSS Software.RESULTS: The present study revealed that majority (56%) sample has mild to moderate burden, (24%) has little or no burden, (19%) has moderate to severe burden and the least (1%) has severe burden. The demographic variables such as educational level, monthly income, training received regarding care of the child were directly associated with psychological burden of the caregivers.CONCLUSIONS: The study concluded that assessing the burden level of caregiver can help them to reduce their burden through proper counselling.